IMPLEMENTASI PROGRAM PEMBELAJARAN MENTORING DALAM PEMBENTUKAN AKHLAK - Fadlilah Anisa Hanifah; S Syamsuddin; Muhammad Fatchurrohman; Meti Fatimah (MAMBA'UL 'ULUM, 2023)
The purpose of this study was to determine the implementation of the mentoring learning program in moral formation. The research is a qualitative research. The subject of research was SDIT Mutiara Insan Sukoharjo. The data collection technique in this study was through observation, interviews and documentation. Then the data analysis in this study used data analysis, namely data reduction, data presentation, and data verification. The results of study indicated that mentoring learning at SDIT Mutiara Insan Sukoharjo is carried a week, on Saturdays, the mentoring learning program must be followed by all students from grade 1 to grade 6 because mentoring learning at SDIT Mutiara Insan Sukoharjo is included in KBM hours. Mentoring learning is guided by the assisted homeroom teacher and is helped the homeroom teacher. There are many supporting factors in this program, starting from finance, facilities, competent teachers and other supports. As for the inhibiting factors, namely: the lack of learning time alloted for mentoring learning and lack of awareness from parents about the importance of implementing of mentoring learning in character building because they are busy work. The general purpose of this mentoring program is to assist and direct students in reviewing and applying religious practices in themselves so that they have noble character that is supported by good knowledge mastery which is then able to practice their knowledge while still being based on true faith.